G, Perawatan GAMBARAN PERAWATAN METODE KANGGURU PADA BAYI BERAT LAHIR RENDAH DI KELURAHAN LILIBA TAHUN 2010 - NI LUH MADE DIAH PUTRI ANGGARAENINGSIH (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
Low birth weight (LBW) is one of the contributors to infant mortality. But infant mortality in LBW infants can be prevented by using simple interventions, inexpensive and appropriate the kangaroo method. This study aims to see the picture of kangaroo care on infant LBW methods at community in distrik Liliba. This qualitative study using in-depth interviews to 7 informants mothers have low birth weight babies. Implementation LBW infant care in addition to the kangaroo method, informants also perform maintenance with oil rubbing Telon, and hot pot.